Home environmental hazards and ageing in place: a scoping review - Muhammad Al-Amin Shaharuddin; Mohd Rizal Abdul Manaf (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ageing in place is a preferable choice for the elderly and it has been adopted as a response to population ageing. The elderly may remain in their own homes so that they can retain connections with friends and family in their community. However, the places in which people grow old often have home environmental hazards that may affect ageing in place. This scoping review aimed to identify environmental hazards that existed in the home of the elderly, factors that were associated with home environmental hazards, and the impact of home environmental hazards on the elderly ageing in place. We used PRISMA-ScR to search PubMed, Web of Science, and Scopus databases. We included all English-language research on home environmental hazards, their associated factors, and impacts on elderly ageing in place. We analysed the study data and summarised the results. 30 records were reviewed, yielding 18 included studies. There was a high prevalence of home environmental hazards in the home of the elderly with the bathroom being the most common location with environmental hazards. Certain factors such as socio-demographic, socioeconomic, living arrangement/house-related factors, and individuals’ health-related factors were associated with the presence of home environmental hazards. Fall was one of the impacts of home environmental hazards though its contribution to the risk of falling remained uncertain. Improved understanding of home environmental hazards and their impact on elderly ageing in place is important so that interventions can be done to reduce the presence and impact of home environmental hazards, and ultimately to protect the elderly’s health.